Pedagogical Framework Versus Traditional Method on Knowledge and Self-Efficacy of Nursing Students Regarding Neonatal Resuscitation: A Randomized Controlled Trial (International Journal of Nursing Education, 2021)
Background: Since its inception, the Neonatal Resuscitation Program (NRP) has been in quest ofevidence-based strategies that promises the best outcome specifically in developing regions. Hence, thepresent study aims to investigate the efficacy of pedagogical framework versus traditional method ofeducation on knowledge and self-efficacy of nursing students regarding neonatal resuscitation.Methods: A randomized controlled trial was conducted between November 2020 to March 2021.The 60 nursing students were randomly assigned to experimental and control groups taught throughtraditional method (Learn, Practice), and LSPPDM Pedagogical (Learn, see, practice, prove, do,maintain) steps respectively. Students were assessed at the baseline and after the intervention usingvalidated questionnaires. Masking of data assessment was provided by assigning a code to each student.ClinicalTrials.gov registration number (NCT04748341).Results: Both knowledge and self-efficacy had been significantly improved (p <0.001) after theintervention. However, the posttest mean change in knowledge scores was significantly higher (p <0.001)in the experimental group (13.3±1.30) as compared to the control (9.97±1.22) with an insignificantdifference (p =0.655) in mean self-efficacy level.Conclusion: Both methods are effective in improving knowledge and self-efficacy. Yet, educationthrough integrating diverse strategies under the umbrella of LSPPDM pedagogy is a more effectiveapproach in enhancing knowledge regarding neonatal resuscitation.